488=42y

Rewrite the equation as 42y=488.

42y=488

Divide 48 by 8.

42y=6

Multiply each term by y and simplify.

Multiply each term in 42y=6 by y.

42y⋅y=6⋅y

Cancel the common factor of y.

Cancel the common factor.

42y⋅y=6⋅y

Rewrite the expression.

42=6⋅y

42=6y

42=6y

Rewrite the equation as 6y=42.

6y=42

Divide each term by 6 and simplify.

Divide each term in 6y=42 by 6.

6y6=426

Cancel the common factor of 6.

Cancel the common factor.

6y6=426

Divide y by 1.

y=426

y=426

Divide 42 by 6.

y=7

y=7

y=7

Solve for y 48/8=42/y